1995
DOI: 10.1093/bja/74.6.643
|View full text |Cite
|
Sign up to set email alerts
|

I.v. tenoxicam for analgesia during Caesarean section

Abstract: We have studied the analgesic efficacy of a single i.v. dose of tenoxicam 20 mg, given 10 min before induction of anaesthesia in 25 patients undergoing elective Caesarean section. Another group of 25 similar patients served as controls. Nalbuphine consumption in the first 24 h after operation was reduced by 50% when tenoxicam was given. The median time to first request for analgesia was increased from 25 to 110 min in the tenoxicam group. Subjective experiences of pain and sedation were significantly greater i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 16 publications
0
38
0
1
Order By: Relevance
“…These results are in agreement with other studies which found no significant increase in bleeding associated with NSAID administration. 1,2,6 We conclude that the intravenous administration of flurbiprofen during anesthesia is effective in reducing postoperative rescue analgesic requirement. Moreover, preoperative flurbiprofen will diminish postoperative pain in a preemptive manner.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…These results are in agreement with other studies which found no significant increase in bleeding associated with NSAID administration. 1,2,6 We conclude that the intravenous administration of flurbiprofen during anesthesia is effective in reducing postoperative rescue analgesic requirement. Moreover, preoperative flurbiprofen will diminish postoperative pain in a preemptive manner.…”
Section: Resultsmentioning
confidence: 76%
“…Elhaki and Nafie 6 showed that intravenous tenoxicam before induction of anesthesia reduced postoperative opioid consumption after Cesarean section. A recent report by Rømsing et al 7 also demonstrated that, for tonsillectomy, preoperative intravenous ketorolac reduced the postoperative use of fentanyl more than postoperative administration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tenoxicam is an NSAID which can be delivered via the intravenous route. It is a potent analgesic and has an established efficacy in the relief of postoperative pain [18][19][20]. Because of its long half-life (60 h), once daily administration is sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated a variety of local anaesthetic techniques in patients undergoing gynaecological laparoscopy [6,7,[17][18][19][20][21]. Seventy-four respondents to our survey used wound infiltration, but despite the simplicity, efficacy and apparent safety of the intraperitoneal administration of local anaesthetic, only 34 did so routinely.…”
Section: Intraperitonealmentioning
confidence: 99%